Effect of heterogenous cattle bull seminal plasma on seminal parameters of mithun - PERUMAL, P; VEERASELVAM, M; RAJORIYA, J S; NAZAR, S; SRIVASTAVA, N; NAHAK, A K (The Indian Journal of Animal Sciences, 2015)
The present study was conducted to assess the effect of replacement of cattle bull seminal plasma with that of mithun bull on seminal parameters of mithun bulls. After collection, the semen samples were divided into group 1 (control): without addition of heterogenous seminal plasma; group 2 to group 5: mithun semen with half and full replacement of good quality cattle seminal plasma and mithun semen with half and full replacement of poor quality cattle seminal plasma, respectively. Individual motility, livability, total sperm abnormality, acrosomal, plasma membrane and nuclear integrity were assessed. The result revealed that there was no significant difference between full and half seminal plasma replacement in both good and poor quality seminal plasma, but the seminal traits of half seminal plasma replacement has nonsignificantly higher value than full seminal plasma replacement. Comparison between the control, half and full seminal plasma replacement of good and half and full seminal plasma replacement of poor quality semen revealed a significant difference.